Managing unintentional iatrogenic Triple Lumen Central Venous Catheter (TLCVC) arterial puncture - M. Shukor, Nurulfida’ Nusaiba; Abdul Rahim, Ezamin; Muda, Ahmad Sobri; Jamil, Hariati; Abduljabbar, Heamn N; Abdul Rahim, Ridzuan (Longe Medikal, 2021)
Unintentional arterial puncture by central venous catheter insertion/placing can result in destructive complications especially if a large bore (>7F) catheter was used. Unplanned immediate catheter ejection with manual external compression is hazardous due to potential torrential blood leakage or formation of a pseudoaneurysm. Endovascular removal with a vascular closure device deployment is preferred in this situation. The aim of this case report is to discuss the alternative strategies if the vascular closure device fails to secure hemostasis.